\"Huashan Rock Art\" dalam konteks sosiobudaya etnik Luoyue, Guangxi, China - Adnan Jusoh (Tanjong Malim, 2019)
\"Huashan Rock Art\" dalam konteks sosiobudaya etnik Luoyue, Guangxi, China by Adnan Jusoh